Factors influencing the posterior tibial slope after medial opening-wedge high tibial osteotomy - Li, Junwei; Yang, Qingqing; Zhang, Min; Yao, Jie; Liu, Bolun; Luan, Yichao; Chen, Yunlin; Fang, Chaohua; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMedial Opening-wedge High Tibial Osteotomy (HTO) is an effective treatment for medial compartment osteoarthritis and knee varus in relatively young and active patients. While it can effectively correct lower limb alignment in the coronal plane, it may also affect the posterior tibial slope (PTS) in the sagittal plane. However, the factors influencing PTS and methods for maintaining PTS stability remain controversial.MethodsA lower limb geometric model was constructed based on the CT data from a patient with medial knee osteoarthritis and varus knee. Multiple models were developed to simulate various conditions: seven different medial cortex inclinations of the proximal tibia (–15°–15°), seven coronal plane inclinations of the central osteotomy plane (–15°–15°), seven sagittal plane inclinations of the hinge axis (–15°–15°), seven hinge axis heights (–7 mm–7 mm), and seven hinge axis inclinations in the axial plane (–15°–15°). Changes in the ratio between anterior and posterior opening gap (RAPOG) and PTS were analyzed.ResultsThe medial cortex inclination of the proximal tibia, coronal plane inclination of the central osteotomy plane, inclination of the sagittal plane of the hinge axis, and height of the hinge axis did not alter the PTS; however, these factors did affect RAPOG, with increased values leading to decrease in RAPOG. The ranges of RAPOG for these factors were 76.37%–54.83%, 68.91%–60.94%, 68.04%–64.08%, and 70.38%–62.61%, respectively. However, the hinge axis inclination on the axial plane affects PTS, for inclinations of –15°, –10°, –5°, 0°, 5°, 10°, and 15°, the PTS decreased 2.48°, 1.83°, 0.98°, 0°, –0.97°, –1.82°, and –2.53°, respectively. To maintain a constant PTS, RAPOG should be readjusted to 65.13%, 66.01%, 66.27%, 65.76%, 65.03%, 65.15%, and 65.57%, respectively.DiscussionThe inclination of the hinge axis in the axial plane affects PTS, as its value increases, PTS also increases. To maintain a constant PTS, RAPOG should be readjusted. Understanding these relationships is essential for optimizing surgical techniques to minimize unintended changes in PTS.